Efektivitas Model Research Based Learning (RBL) Pada Mata Kuliah Statiska 2 Terhadap Hasil Belajar Mahasiswa Perbankan Syariah - Mahfudhotin (Comprehensive Journal of Islamic Studies, 2024)
This research was motivated by the observation that the dominant lecture method in teaching statistics 2 courses resulted in minimal student understanding. Students' lack of understanding of the application of data analysis techniques studied in this course is due to several factors, such as the complexity of the material, lack of interest, and ineffective learning methods. To overcome this problem, a learning strategy approach was taken which has been proven to be an appropriate learning strategy and in accordance with student characteristics which is able to increase understanding of the material being taught. The learning strategy used is the Research Based Learning (RBL) technique. RBL is a learning technique that uses research aspects in the learning process. In its application, students learn to actively look for research articles for analysis-synthesis as well as material for creating research articles according to the material being taught. The research method uses the Quasi Experimental Research method with a Pretest-posttest Control Group Design which aims to design a learning model for the statistics 2 course that is integrated with technology in improving the learning of Sharia Banking students. By implementing research-based learning, students' critical and creative thinking skills in statistics material are expected to improve.